PENDAMPINGAN LITERASI SAINS DALAM MENDORONG PENINGKATAN PENGETAHUAN MASYARAKAT TAMBRAUW - Zulkarnain Sangadji; Ihsan Febriadi; Muhammad Syahrul Kahar (Universitas Mataram, 2023)
Tambrauw Regency is one of the regencies in Indonesia's Southwest Papua Province. The partner's problems are related to literacy, science and digital literacy which are conceptually needed by the community. A UNESCO survey in 2011 showed that the reading culture of people in Indonesia was in the lowest position compared to countries in ASEAN with a value of 0.001. Low interest in reading is closely related to low literacy. Urgency in service: (1) needs to be encouraged in strengthening the aspect of increasing literacy skills for students and communities there, (2) more serious and sustainable efforts need to be made in maintaining forest sustainability and reducing adverse impacts on the environment, (3) digitalization of assistance to the fulfillment and welfare needs of the community. The purpose of dedication is to analyze how much the level of empowerment of partners has increased. The method in carrying out this service is the method of discussion. The results of the activity showed that critical land rehabilitation activities involving 10 community members with material delivery methods and practices of fertilizer making and land processing showed a significant increase in community knowledge. Pre-test and post-test data indicate that most participants have been able to increase their understanding of the importance of preserving agricultural ecosystems with an improvement category categorized as